Abdominal wall ectopic testis - Case report and review of literature - Vinod Raj; Rajeev Redkar; Shirin Joshi (Elsevier, 2018)
Undescended testis is a common condition which affects about 2-4% of male infants and more commonly seen in preterm infants. The descent of testis is a complex process which requires cross talk between various hormones and testes. Undescended testis is where a testis has been arrested in its normal pathway of descent due to various factors. Ectopic testis is the one which has deviated from its normal pathway of descent. Abdominal testis is the rarest form of ectopic testis which has been reported in literature. To the best of our knowledge 6 cases have been reported till date. Keywords: Undescended testis, Ectopic testis, Abdominal wall hernia, Abdominal ectopic testis, Laparoscopic orchidopexy and open orchidopexy